MyAttend: Development of Mobile-based Attendance System with Anonymization Approach to Preserve Location Privacy - Theviksha A/P Sannasi; Abdul Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2022)
Due to Covid-19 results many people to start working from home which made it difficult to keep track of their attendance. When tracking the attendance, users are required to store their personally identifiable information (PII). Therefore, a mobile based attendance system with location anonymization is developed to allow employer to track staff’s attendance at the same time protect their privacy. Prototyping model is used as the methodology to develop MyAttend with five phases which are planning, analysis, design implementation and testing. This application is developed using Android Studio and includes login module, manage employer/ staff module, manage profile module, attendance module and payroll module. The system allows admin to manage employer and manage staffs, employer to manage staffs, review staffs’ attendance record and calculate payroll and staffs to record their attendance, view their payroll and update personal information. The significance of project is to record user location data anonymously using generalization and masking out technique.